2013
DOI: 10.1016/j.jhin.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Trends, risk factors and outcomes of healthcare-associated infections within the Italian network SPIN-UTI

Abstract: The study highlighted the increased risk of HAI, at least partially explained by the greater severity and number of hospitalized patients requiring ICU admission. Furthermore, the management of intubation procedures and of ventilated patients was identified as a potential target for infection control interventions to decrease the growing risk of HAI in ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…12 ). Numerous multi-centre studies confirm the consistency of these results with the outcomes presented in this study [11][12][13][14] . However, a detailed data review indicates differences in the HAI epidemiology between Polish ICUs and the HAI-Net data, which may be related to the organization of work and the system of HAI surveillance.…”
Section: Discussionsupporting
confidence: 88%
“…12 ). Numerous multi-centre studies confirm the consistency of these results with the outcomes presented in this study [11][12][13][14] . However, a detailed data review indicates differences in the HAI epidemiology between Polish ICUs and the HAI-Net data, which may be related to the organization of work and the system of HAI surveillance.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, benchmarking of HAIs surveillance protocols in NICUs is available on a national scale for NHSN [4][5][6], NEO-KISS [10,11], the Vermont Oxford Network [7,8], the neonIN network [12], and the Canadian Neonatal network [9]. A national framework for the surveillance of HAIs in Italy-SPIN-UTI project is active in Italy since 2008, which involves adult Intensive care units (ICUs) with none of NICUs [13,14]. Although no surveillance network for HAIs in NICUs is present in Italy, few studies reported the prevalence [15], incidence of HAIs [16][17][18][19][20] and epidemics of specific nosocomial pathogens [20][21][22][23][24] in selected Italian NICUs.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…In Europe, the most recent report of the European Antimicrobial Resistance Surveillance Network (EARS-Net) describes a general increase of AMR in the Gram-negative pathogens including Klebsiella pneumoniae and A. baumanni [ 1 ]. In Italy, the results of the Italian Nosocomial Infections Surveillance in Intensive Care Units (SPIN-UTI) network revealed that K. pneumoniae and A. baumanni are among the most commonly isolated microorganisms in intensive care unit (ICU)-acquired infections [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%